Fecal Transplant Sustained Colitis Remission on Immunotherapy Resumption - Rajan Amin; Anusha S. Thomas; Yinghong Wang (Annals of Internal Medicine: Clinical Cases)
Immune checkpoint inhibitors are increasingly used to treat various cancers, but they can cause immune-related adverse events that lead to treatment cessation. Here we report 2 cases of immune-mediated colitis that were treated with fecal microbiota transplant. Both cases had sustained colitis remission, which allowed resumption of immunotherapy.